Shared Decision Making in Surgery: A Meta-Analysis of Existing Literature - Niburski, Kacper; Guadagno, Elena; Abbasgholizadeh-Rahimi, Samira; Poenaru, Dan (The patient : patient-centered outcomes research, 2020)
Background Shared decision making (SDM) is a popular care paradigm between patients and clinicians to facilitate treatment agreement by building consensus and sharing information. Decisional aids (DAs) are tools frequently used in SDM for improving knowledge sharing and facilitating the decision process. The use and outcomes of decisional aids in surgery, however, have not been investigated. This study investigates whether SDM in surgery benefits any type of surgical patient compared with non-SDM treatment using patient-defined outcomes, such as an increase in knowledge and decisional satisfaction, as well as decreased decisional regret and anxiety. Methods The search strategy was developed with a medical librarian to address the question of whether SDM in surgery benefits any type of surgical patient compared with non-SDM treatment using patient-defined outcomes. Seven databases (Medline [Ovid], Embase [Ovid], Cochrane [Wiley], Africa-Wide [EBSCO], Global Health [Ovid], Global Index Medicus (WHO), Web of Science [Clarivate Analytics]) were searched from inception until September 9th, 2019, with no language restriction. A two-person title and abstract screen was performed, followed by a full-text publication review. A DerSimonian–Laird random effects model was used for the meta-analysis, with heterogeneity established. Mean and standard deviation were collected for all study outcomes. Study eligibility was determined with strict inclusion and exclusion criteria. Study quality was assessed using the Cochrane Bias Risk Assessment Tool. Results In total, 6060 studies were retrieved. After duplicates were removed, 5303 titles and abstracts were screened, and of 356 full texts reviewed, 42 studies were included in the analysis. Heterogeneity was high in three of six variables (surgery chosen, decisional conflict, and knowledge gained), moderate in two (decisional anxiety and decisional satisfaction), and low in one (decisional regret). For all except the rates of surgical intervention, the results for decisional conflict, knowledge gained, decisional satisfaction, and decisional anxiety were significant at a 95% confidence interval. Decisional conflict decreased in 20/24 of the papers that recorded it; rates of choosing surgery decreased in 8 of the 11; and patient knowledge increased in 19 of the 22 that recorded it. The majority of papers had risk of bias, however, with the evidence of generally low quality. Conclusion The results suggest that SDM in surgery is associated with greater quality of patient satisfaction and value agreement, leading to decreased conflict and anxiety, and increased knowledge and translation. This data is useful in guiding the development of SDM protocols for use in surgical disciplines. Review Registration Registered on PROSPERO—ID: CRD42018097286 [13]. Plain Language Summary Shared decision making (SDM) has been used in various healthcare disciplines to benefit patient care but has not been explored in surgical disciplines. This study investigated whether SDM in surgery benefits surgical patients compared with non-SDM treatment using patient-defined outcomes. Patients who used SDM in surgery were found to have less conflict and more satisfaction making decisions, as well as increased knowledge about their surgery compared with non-SDM patients. This study suggests that SDM is likely to benefit surgical patients to have better care outcomes.